Post-traumatic stress disorder, anxiety and depression in post-COVID19 patients: integrative review - Carrijo, Marilúcia; Cãndida Oliveira, Miriã; C. Oliveira, Aline; Eduarda Moreira Lino, Maria; K. A. Souza, Shayra; R. Afonso, João Pedro; S. Moura, Ricardo; R. P. Fonseca, Daniela; L. Fonseca, Adriano; S. R. Tomaz, Renata; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Global estimates point to high prevalence of neuropsychiatric disorders in individuals hospitalized for COVID-19. In Brazil, anxiety and depression rates resulting from SARS-CoV-2 infection range from 29.7% to 68%, respectively, being more prevalent in young women, with lower educational level, with comorbidities and psychological problems. previous. Objective: Identify possible causes, verify prevalence and identify risk factors for anxiety, depression and post-traumatic stress disorder (PTSD) in patients hospitalized for COVID-19. Methods: An integrative literature review was carried out involving retrospective and/or prospective cohort studies and population-based clinical trials published in the last three years. The main evidence on the relationship between neuropsychiatric disorders and intrinsic changes in neuroimmunomodulation parameters was also raised. Results: Twenty-one studies were included that addressed the presence of symptoms of PTSD, anxiety, depression, fatigue in sleep disorders in COVID19 survivors. Conclusion: With this literature review, it can be concluded that PTSD, anxiety, depression, fatigue and sleep disturbances are highly prevalent symptoms in COVID-19 survivors, being persistent for up to one-year post-infection.